Microbial fuel cell (MFC) in treating spent caustic wastewater: varies in hydraulic retention time (HRT) and mixed liquor suspended solid (MLSS) - Norsafiah, Fazli; Noor Sabrina, Ahmad Mutamim; Nur Maizatul, Azwan; Nurul Aisyah, Mohd Ramli
The performance of an anoxic-aerobic MFC reactor operated with spent caustic wastewater was studied at different HRT and MLSS. Spent caustic wastewater is the industrial wastewater with high COD concentration influenced by its high sulfur content, high salinity and high alkalinity. Little is known on the MFC capacity in treating spent caustic wastewater, therefore the present study employed spent caustic wastewater as the feed wastewater. The MFC performance was evaluated in terms of voltage production, COD and sulfide removal efficiency. The HRT range tested were 7 days, 8 days and 9 days whereas the MLSS range tested were 1500 mg/L, 2000 mg/L and 2500 mg/L. From the study, HRT of 9 days was the optimum HRT for the MFC operation with the highest COD and sulfide removal efficiency of 98% and 98.98% respectively. The removal efficiency increased with increasing HRT. In terms of voltage production, the highest achievable voltage was 82.1 mV obtained at HRT of 9 days. The overall energy production trend shows that energy production was increased with increasing HRT. For MLSS study, the optimum MLSS for the MFC operation was at 1500 mg/L with the highest COD removal and sulfide removal efficiency of 94.07% and 89.01% respectively. In terms of voltage production, the highest achievable voltage was 36.7 mV obtained at MLSS of 2500 mg/L.